Step
*
1
4
1
1
1
4
of Lemma
rcos-seq-differences
1. n : ℕ
2. 0 < n
3. e : {e:ℝ| r0 < e} 
4. x : ℝ
5. x ∈ [rcos-seq(n - 1), rcos-seq(n)]
6. v : ℝ
7. rcos-seq(n) = v ∈ ℝ
8. v1 : ℝ
9. rcos-seq(n - 1) = v1 ∈ ℝ
10. x1 : {x:ℝ| x ∈ [r0, rcos-seq(n)]} 
⊢ r0 ≤ rcos(x1)
BY
{ (D -1 THEN Unhide THEN Auto) }
1
1. n : ℕ
2. 0 < n
3. e : {e:ℝ| r0 < e} 
4. x : ℝ
5. x ∈ [rcos-seq(n - 1), rcos-seq(n)]
6. v : ℝ
7. rcos-seq(n) = v ∈ ℝ
8. v1 : ℝ
9. rcos-seq(n - 1) = v1 ∈ ℝ
10. x1 : ℝ
11. x1 ∈ [r0, rcos-seq(n)]
⊢ r0 ≤ rcos(x1)
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  0  <  n
3.  e  :  \{e:\mBbbR{}|  r0  <  e\} 
4.  x  :  \mBbbR{}
5.  x  \mmember{}  [rcos-seq(n  -  1),  rcos-seq(n)]
6.  v  :  \mBbbR{}
7.  rcos-seq(n)  =  v
8.  v1  :  \mBbbR{}
9.  rcos-seq(n  -  1)  =  v1
10.  x1  :  \{x:\mBbbR{}|  x  \mmember{}  [r0,  rcos-seq(n)]\} 
\mvdash{}  r0  \mleq{}  rcos(x1)
By
Latex:
(D  -1  THEN  Unhide  THEN  Auto)
Home
Index